EXPERIENCES IN THE AMAZON: INTERNSHIP IN INDIGENOUS HEALTH IN THE FORMATION OF FAMILY AND COMMUNITY DOCTOR - Costa Silva, Lays (Health and Society, 2024)
The text explores the formation of family and community doctors with a specific focus on acting in rural areas and the health of the indigenous population, a frequently neglected aspect in residency programs in large urban centers. The narrative details an internship at the Macapá Indigenous Health Support House (Casai) and at the base hub of the Manga village, located in Oiapoque, Amapá. During this internship, the resident doctor of the municipality of Rio de Janeiro-RJ had the opportunity to provide medical attention directly to indigenous communities of the villages of Amapá and northern Pará. A central aspect of the text is the importance of exchange between scientific knowledge and traditional indigenous practices. The respect demonstrated by the indigenous population and the credibility attributed to their beliefs were essential to the effectiveness of the care performed. This experience offered the resident significant learning about person -centered medicine, allowing enriching contact with different cultures and traditions. These cultures have unique visions and understandings about the process of getting sick and healing, which contributed to a broader and more integrated understanding of health care. The internship stressed the importance of recognizing and respecting cultural practices in medical practice.